MENINGKATKAN PENGUASAAN KONSEP SISWA SMP PADA MATERI RELASI DAN FUNGSI DENGAN PENDEKATAN SAINTIFIK - Umar, Novia Firdayanti; Afrilianto, M. (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research is motivated by the low understanding of students' mathematical concepts due to the lack of active participation of students during the learning process. The purpose of this classroom action research is to examine the increase in the ability of students to understand concepts in mathematics learning about Relationships and Functions using the Scientific approach. This research was conducted on 20 students of class VIII SMP Advent Cimindi. This classroom action research was designed in 2 cycles consisting of 4 meetings. The procedure in each cycle includes the stages: planning the action, implementing the action, observing and reflecting. The effectiveness of the action in each cycle is measured from the results of observations of students and teachers during learning and from student learning evaluations. The results showed that the application of a scientific approach could improve students' ability to understand mathematical concepts. This is indicated by an increase in student learning completeness from the first cycle to the second cycle. In the first cycle, the level of student learning completeness reached 55% and in the second cycle increased to 90%. So it can be concluded that learning with a scientific approach can improve students' ability to understand mathematical concepts.